Digital learning across cultures: an account of activity theory. Issue 4 (3rd July 2020) - Guo, Karen; Bussey, Francesca; Adachi, Chie
ABSTRACT: This paper explores a teaching and learning process as it unfolds in an online offshore classroom. The paper reports on teaching and learning narratives distilled from different cultures, namely the cultures of educators and students in the context of digital learning environments. Drawing on activity theory as a conceptual framework to analyse the narrative, we employ self-study as a methodological tool for capturing the dynamism and complexities that unravel in intercultural and technology-enabled teaching activities. The framework explores the relationships, tensions and opportunities of diverse activity elements that constitute the design and delivery of digital pedagogies. In the networked intercultural system, sustaining the position of activity elements and the specific relational circuit that they institutionalise is a key task for understanding digital technologies as an influential tool for effective learning and teaching practices. We argue that seeing the digital platform from the perspective of its role in creating dynamic interrelationships in a complex activity system is one way to move beyond the cultural confines of any particular element in the system.